Masquerade Syndrome of Multicentre Primary Central Nervous System Lymphoma - Silvana Guerriero; Ermete Giancipoli; Lorenza Ciracì; Giuseppe Ingravallo; Marcella Prete; Elisabetta Di Leo; Antonietta Cimmino; Nicola Cardascia (Case Reports in Ophthalmological Medicine)
Purpose. In Italy we say that the most unlucky things can happen to physicians when they get sick, despite the attention of colleagues. To confirm this rumor, we report the sad story of a surgeon with bilateral vitreitis and glaucoma unresponsive to traditional therapies. Methods/Design. Case report. Results. After one year of steroidal and immunosuppressive therapy, a vitrectomy, and a trabeculectomy for unresponsive bilateral vitreitis and glaucoma, MRI showed a multicentre primary central nervous system lymphoma, which was the underlying cause of the masquerade syndrome. Conclusions. All ophthalmologists and clinicians must be aware of masquerade syndromes, in order to avoid delays in diagnosis.